Effect of ischemia/reperfusion on the rat intrarenal renin-angiotensin system. - Kontogiannis, Jimmy. (University of Ottawa (Canada), 1997)
Proliferation and differentiation of tubular cells occur after renal ischemia/reperfusion. Angiotensin II has multiple growth effects on different renal cell types, and also regulates renal blood flow In particular, proximal tubular cells locally synthesize angiotensin II, which can bind to AT$\sb1$ receptors in an autocrine/paracrine fashion. The function of the AT$\sb2$ receptor is unknown, but is linked to apoptosis in other tissues. In the current study, gene expression for intrarenal angiotensinogen, cortical AT$\sb1$ receptor and proximal tubular AT$\sb1$ receptor was determined by Northern blots, and gene expression for the AT$\sb2$ receptor was determined by RT-PCR. In rats after ischemia/reperfusion. A significant downregulation of angiotensinogen mRNA occurred from 6 to 72 hours post-ischemia/reperfusion, whereas the cortical AT$\sb1$ receptor did not change significantly. In contrast, proximal tubular AT$\sb1$ receptor mRNA significantly decreased from 0 to 24 hours post-ischemia/reperfusion, and recovered after 72 hours. New gene expression for the AT$\sb2$ receptor was observed in ischemic proximal tubular segments and in the ischemic outer medulla 120 hours after ischemia/reperfusion. By histoautoradiography, a significant decrease in the density of angiotensin II binding was noted in the ischemic cortex after 24 hours post-ischemia/reperfusion, and in the outer medulla at 3 and 24 hours. At 120 hours post-ischemia/reperfusion, intrarenal angiotensin II levels, density of angiotensin II binding and angiotensinogen gene expression recovered. In conclusion, the intrarenal renin-angiotensin system is downregulated with ischemia/reperfusion, and recovers 120 hours post-ischemia/reperfusion, with co-expression of AT$\sb1$ and AT$\sb2$ receptor mRNA at this time. These findings suggest that co-expression of AT$\sb1$ and AT$\sb2$ receptors may be involved in the remodelling of injured tissue.
Keywords: Biology, Animal Physiology.